2010
DOI: 10.1038/ni.1842
|View full text |Cite
|
Sign up to set email alerts
|

TRPV2 has a pivotal role in macrophage particle binding and phagocytosis

Abstract: Macrophage phagocytosis is critical for defense against pathogens. Whereas many steps of phagocytosis involve ionic flux, the underlying ion channels remain ill-defined. Here, we show that zymosan-, IgG-, and complement-mediated particle binding and phagocytosis are impaired in macrophages lacking the cation channel, Transient Receptor Potential Vanilloid 2 (TRPV2). TRPV2 is recruited to the nascent phagosome and depolarizes the plasma membrane. Depolarization increases phosphatidylinositol-4,5-bisphosphate (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
252
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 247 publications
(273 citation statements)
references
References 39 publications
10
252
0
1
Order By: Relevance
“…24,40,42 Membrane depolarization has been shown to activate the PI3K-Akt signaling in neuronal cells. 43,44 Link et al 45 have reported that TRPV2 activity induces membrane depolarization during immune complex-induced phagocytosis. We hypothesized that the influx of Na þ through Trvp5/6 under the low [Ca 2 þ ] condition may lead to membrane depolarization, which in turn increases IGF signaling in these cells.…”
Section: Discussionmentioning
confidence: 99%
“…24,40,42 Membrane depolarization has been shown to activate the PI3K-Akt signaling in neuronal cells. 43,44 Link et al 45 have reported that TRPV2 activity induces membrane depolarization during immune complex-induced phagocytosis. We hypothesized that the influx of Na þ through Trvp5/6 under the low [Ca 2 þ ] condition may lead to membrane depolarization, which in turn increases IGF signaling in these cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies suggest that TRPV2 is activated by insulin-like growth factor (Kanzaki et al, 1999). Link et al (2010) reported that TRPV2-deficient macrophages are defective in chemoattractant-elicited motility and phagocytosis. Further investigation is required to elucidate the role of TRPV2 in terms of the proliferation of HSCs stimulated by various growth factors.…”
Section: A B Cmentioning
confidence: 99%
“…TRPV2 expression has been observed in TRPV1-negative medium-to large-diameter neurons of the rat dorsal root and trigeminal ganglia and possibly in thinly myelinated nociceptors (Caterina et al, 1999;Lewinter et al, 2008). However, TRPV2 mRNA or immunoreactivity has also been detected in the brain, autonomic ganglia, spinal cord, skeletal and vascular myocytes, visceral organs (including the intestine, pancreas, spleen, and bladder), and blood cells (Caterina et al, 1999;Ichikawa and Sugimoto, 2001;Muraki et al, 2003;Kashiba et al, 2004;Lewinter et al, 2004;Inada et al, 2006;Lewinter et al, 2008;Hisanaga et al, 2009;Zanou et al, 2009;Link et al, 2010). TRPV2 expression may also be involved in the migration and proliferation of cancer cells (Caprodossi et al, 2008;Monet et al, 2010), and TRPV2-positive neurons observed in the rat myenteric plexus may be IPANs (Kashiba et al, 2004).…”
Section: Introductionmentioning
confidence: 98%